2009
DOI: 10.1016/j.ejcts.2009.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Superior flow for bridge to life with self-expanding venous cannulas

Abstract: The negative pressure required to achieve adequate venous drainage with the self-expanding venous cannula accounts for approximately 31% of the pressure necessary with the 19 F rectilinear cannula. In addition, a pump flow of more than 4 l min(-1) can be achieved with the self-expanding design and a well-accepted negative inlet pressure for minimal blood trauma of less than 50 mmHg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…There are few investigations of flow dynamics in vivo. 8-11 Theoretical studies in vitro are also rare because of difficulties in making mock circuits for low pressure and a highly collapsible environment, such as the venous system. 12,13 “L”-shaped end-hole venous drainage cannulas were used in the early days of cardiovascular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There are few investigations of flow dynamics in vivo. 8-11 Theoretical studies in vitro are also rare because of difficulties in making mock circuits for low pressure and a highly collapsible environment, such as the venous system. 12,13 “L”-shaped end-hole venous drainage cannulas were used in the early days of cardiovascular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Toomasian and McCarthy 3 used femorofemoral CPB assisted by a centrifugal pump in 50 patients. 15 The second study was also made in vivo using a portable extracorporeal oxygenator and a self-expanding cannula. Cannulas used for that study ranged from 18F to 28F.…”
Section: Discussionmentioning
confidence: 99%
“…The first one showed that, with an 18F self-expanding cannula, the theoretical blood flow in animals going through CPB was achieved with a negative pressure of less than j50 mm Hg. 15 The second study was also made in vivo using a portable extracorporeal oxygenator and a self-expanding cannula. The results showed that, with a negative pressure of j43 mm Hg, the theoretical blood flow could be reached with an 18F selfexpanding cannula.…”
Section: Discussionmentioning
confidence: 99%
“…When used for cardiopulmonary bypass, they were found to improve flow speeds and reduce venous line pressures. 20 The disadvantage is the difficulty of removal, especially when used for prolonged periods of time.…”
Section: The Ideal Cannula Designmentioning
confidence: 99%